A note on dispersing particles on a line. Issue 4 (29th October 2018) - Frieze, Alan; Pegden, Wesley
Abstract : We consider a synchronous dispersion process introduced in pervious study of Cooper and coworkers and we show that on the infinite line the final set of occupied sites takes up O ( n ) space, where n is the number of particles involved.